Relationship between social support of parents and self concept with stability of career decision - Regina BM Nainggolan; Firman Firman; Yeni Karneli (International Conferences on Educational, Social Sciences and Technology)
Background of this study is motivated by the students who have many problems about have no readiness, have no knowledge, and have not been informed about employment opportunities in out of school education. The study aims to reveal that there is a relationship between parental social support and self concept with stability of career decision. The study uses quantitative method of correlational. The Subject of this study is a consisting of 75 people. The research instrument used is a questionnaire and used a Likert scale. The data of this study are analyzed using multiple regression. The results of this study indicate that there is a very significant relationship between social support of parents, Self Concept with Stability of Career Decision.